PENGELOLAAN KELOMPOK DALAM PEMBINAAN USAHA TANI MASYARAKAT DI DESA CIKOWANG KECAMATAN MANGARABOMBANG KABUPATEN TAKALAR: GROUP MANAGEMENT IN COMMUNITY FARMING BUSINESS DEVELOPMENT IN CIKOWANG VILLAGE, MANGARABOMBANG DISTRICT, TAKALAR REGENCY - Beddu, Hartina (Faculty Of Law Bosowa University, 2020)
That the management of the group through the development of agriculturalhuman resources is very important, because with coaching someone will know about good and bad, right and wrong attitudes so that the end becomes a habit that can be meaningful in life and community life. This study aims to analyze the management of groups in fostering farming, group fostering in growing farms and fostering groups in developing business fostering groups in the development of farming. This research was conducted in Cikowang Village, Mangarabombang District, Takalar Regency with a qualitative descriptive study describing events in detail in the form of narration using proportional samples based on the area of mastery of rice fields. The research sample consisted of 234 respondents consisting of 105 respondents who controlled narrow rice fields, medium respondents 82 respondents and 47 respondents who had extensive observation, through questionnaires, free questionnaires and interviews with data analyzed using cross tabulation. The results showed that: 1) group management in fostering farming businesses, the management is very effective because it reaches 98.21 percent, 2) group guidance in growing farming businesses, is very effective at 98.29 percent and 3) group guidance in developing farming businesses, the coaching was very effective, reaching 97.61 percent. Suggestions: 1) group management in fostering farming is enhanced by the togetherness of members. 2) further enhancing the development of farming through cooperation so as to obtain satisfactory results. 3) guidance in developing agricultural businesses, especially partnerships and marketing of business products.